Evaluating the Carbon Footprint of Cement Plants Integrated With the Calcium Looping CO2 Capture Process - Carbone, Claudio; Ferrario, Daniele; Lanzini, Andrea; Stendardo, Stefano; Agostini, Alessandro (Frontiers in Sustainability, 2022)
Cement industry is estimated to account for approximately 6-7% of anthropogenic CO2 emissions globally. Therefore, the identification of innovative solutions for their mitigation is both a priority and a challenge. The integration of carbon capture and storage technologies into the industrial production process is considered among the most viable solutions for this purpose, and Calcium Looping (CaL) represents one of the most promising. A key research challenge points to maximize process efficiencies and minimize production cost to decouple cement production from carbon emissions. The carbon capture process proposed in this work is a looping system where CO2 is absorbed by calcium oxide (CaO) in the first reactor (carbonator), and the calcium carbonate (CaCO3) produced is regenerated in an oxy – fired calciner. During calcination, CO2 is released from the sorbents, purified, compressed and then made available for geological storage. In this study, greenhouse gas (GHG) emissions related to two cement production systems with CaL carbon capture are evaluated: the tail end CaL carbon capture and the integrated CaL carbon capture. The carbon footprint is complemented with the assessment of the resources depletion mineral and elements and the demand of primary energy. An eco-design approach was pursued by carrying out a life cycle assessment to identify the environmental hot-spots and which CaL integration approach presents a higher potential for cement industry decarbonization. The results of the analysis were compared to a conventional cement production process. The results show that the GHG emissions may be reduced by 74% with a tail-end approach and 71% when the CaL is fully integrated into the cement production process. When a future perspective, with higher penetration of renewable energy resources into the electricity sector, was modelled, the results showed that CaL integrated into the clinker production process is more promising in terms of reduction of the carbon footprint, rather than the tail end solutions. Primary energy consumption from non-renewables is substantially impacted by CaL, with the integrated CaL configuration showing to be a more efficient solution because of less primary energy consumption (coal).